2011
DOI: 10.2174/1876525401103010006
|View full text |Cite
|
Sign up to set email alerts
|

Association between Self-Perceived Health, Physical Activity, and BMD in Aging Men and Women

Abstract: Abstract:The association between general health and bone mineral density (BMD, g/cm 2 ) is not well studied. The purpose of this study was therefore to examine the relationships between BMD, self-perceived health, and lifestyle factors in a well-defined cohort of middle-aged men and women. The cohort studied consisted of 1595 women and men with a mean age of 57 years at baseline (range 30-74 yr), who completed a comprehensive health survey within the Västerbotten Intervention Project. BMD was measured at the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Concerning the association among BAS factors, satisfaction with appearance and body satisfaction level, the results found here were similar to other studies that found a strong relationship between satisfaction with appearance and body appreciation (Barreto, Fernandes, & Guihard-Costa, 2011;Whitbourne & Whitbourne, 2001).The difference in body appreciation between sedentary and physically active participants is also worth mentioning. Physical activity is an unquestionable source of experience with the body, and the possibility of experiencing the limits and the possibilities of the body -especially as the living body changes with age -is important for developing body image (Tavares, 2003). This theoretical argument explains this finding, which is important to all physical edicator to consider, since they are the professional that took care of this dimension of life.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Concerning the association among BAS factors, satisfaction with appearance and body satisfaction level, the results found here were similar to other studies that found a strong relationship between satisfaction with appearance and body appreciation (Barreto, Fernandes, & Guihard-Costa, 2011;Whitbourne & Whitbourne, 2001).The difference in body appreciation between sedentary and physically active participants is also worth mentioning. Physical activity is an unquestionable source of experience with the body, and the possibility of experiencing the limits and the possibilities of the body -especially as the living body changes with age -is important for developing body image (Tavares, 2003). This theoretical argument explains this finding, which is important to all physical edicator to consider, since they are the professional that took care of this dimension of life.…”
Section: Discussionmentioning
confidence: 97%
“…Because the perception of age-related changes in particular is linked with ADL performance, which demands both physical and cognitive effort from the aging individual, it would seem that the perception of aging seems to be a complex product of such activities (Nagel, Werkle-Bergner, Li, & Lindeberger, 2007). An active, healthy lifestyle affects one's self-perception of health and, consequently, healthy aging (Nagel et al, 2007;Tervo, Nordström, & Nordström, 2011). We also found differences in the frequency of health problems and their relation to aging in the sedentary and active groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that individuals who are physically active have a better perception of their health status [20,21].…”
Section: Discussionmentioning
confidence: 99%